2019
DOI: 10.3390/cells8050384
|View full text |Cite
|
Sign up to set email alerts
|

Protein Hydroxylation by Hypoxia-Inducible Factor (HIF) Hydroxylases: Unique or Ubiquitous?

Abstract: All metazoans that utilize molecular oxygen (O2) for metabolic purposes have the capacity to adapt to hypoxia, the condition that arises when O2 demand exceeds supply. This is mediated through activation of the hypoxia-inducible factor (HIF) pathway. At physiological oxygen levels (normoxia), HIF-prolyl hydroxylases (PHDs) hydroxylate proline residues on HIF-α subunits leading to their destabilization by promoting ubiquitination by the von-Hippel Lindau (VHL) ubiquitin ligase and subsequent proteasomal degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 146 publications
(250 reference statements)
1
163
0
1
Order By: Relevance
“…In contrast to established mechanisms of non-HIF hydroxylation targets of FIH, like Ovarian tumor domain containing ubiquitin aldehyde binding protein 1 (OTUB1), non-HIF hydroxylation targets of PHDs are less well characterised. It is known that molecules of the NF-κB pathway and zinc fingers and homeoboxes 2 (ZHX2) are hydroxylated by PHDs but the exact mechanisms and especially a role in muscle regeneration are yet unknown [40]. Regarding the NF-κB pathway, we and others have shown that inhibition of PHDs (although this is mostly directed via PHD1 in the so far analysed settings) induces an activation of the classical NFκB pathway [41].…”
Section: Resultsmentioning
confidence: 94%
“…In contrast to established mechanisms of non-HIF hydroxylation targets of FIH, like Ovarian tumor domain containing ubiquitin aldehyde binding protein 1 (OTUB1), non-HIF hydroxylation targets of PHDs are less well characterised. It is known that molecules of the NF-κB pathway and zinc fingers and homeoboxes 2 (ZHX2) are hydroxylated by PHDs but the exact mechanisms and especially a role in muscle regeneration are yet unknown [40]. Regarding the NF-κB pathway, we and others have shown that inhibition of PHDs (although this is mostly directed via PHD1 in the so far analysed settings) induces an activation of the classical NFκB pathway [41].…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, PHDs are multifunctional proteins. Besides HIF-αs, PHDs interact with some proteins, including GCN5, IKKβ, MAPK6, p53, and FOXO3a, and regulate their functions by hydroxylase activity-dependent and independent mechanisms [ 35 , 36 ]. For example, PHD3 suppresses IKKβ/NF-kB signaling in a mechanism not requiring its hydroxylase activity [ 36 ], and PHD-dependent regulation of HIF-αs is dependent of hydroxylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of the hypoxia-inducible factor (HIF) prolyl hydroxylase (PH) enzyme are a new class of agents for the treatment of anemia [142]. HIF is hydroxylated by HIF-PH to cause its degradation [143]. On the other hand, HIF is reported to play important roles in cell-cycle regulation of HSC and production of EPO.…”
Section: Lpa Receptor Agonists and Antagonists As Potential Treatmentmentioning
confidence: 99%